Crystal structure of (4-methylbenzyl)(triphenyl)phosphonium chloride dihydrate, C26H28ClO2P - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open [Commercial Publisher], 2021)
C26H28ClO2P, monoclinic, P21/c (no. 14), a = 11.6061(2) Å, b = 19.7791(4) Å, c = 11.1982(3) Å, β = 116.278(3)°, V = 2304.98(10) Å3, Z = 4, Rgt(F) = 0.0373, wRref(F2) = 0.1034, T = 100 K.